CUSTOMER SATISFACTION LAST MILE DELIVERY IN ECOMMERCE SUPPLY CHAIN: STUDY ON SHOPEE AND TOKOPEDIA - Nasywa Natania; Abdurrahman Faris Indriya Himawan (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
The continuous expansion of Indonesia’s e-commerce market has made last-mile delivery a decisive factor in shaping customer experience. As competition intensifies between Shopee and Tokopedia, delivery performance increasingly influences how customers evaluate their shopping experience and whether they choose to repurchase. Although both platforms have strengthened their logistics systems and digital capabilities, issues related to delivery punctuality, reliability, cost transparency, and courier service quality remain evident. This research explores how different aspects of last-mile delivery contribute to customer satisfaction and examines whether these relationships differ between the two platforms. Drawing upon Expectation-Confirmation Theory and supported by service quality perspectives, the study focuses on delivery speed, delivery reliability, tracking visibility, courier professionalism, and delivery cost as key variables. A quantitative explanatory approach was adopted through survey distribution to active e-commerce users in Indonesia. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM), followed by Multi-Group Analysis. The findings are expected to provide empirical insights into the delivery attributes that most strongly influence customer satisfaction while supporting academic discussions on e-commerce logistics and managerial decision-making to improve last-mile delivery performance.